Vertical electrical sounding as an exploration technique to improve on the certainty of groundwater yield in the fractured crystalline basement aquifers of eastern Uganda. & A. & P.W. & M. - Batte, A.G.; Muwanga, A.; Sigrist, P.W.; Owor, M. (Hydrogeology journal, 2008)
Groundwater in eastern Uganda mostly occurs in fractures in the crystalline basement rocks and at the interface between the overburden and bedrock. The study was aimed at improving the success rate of boreholes through the use of complimentary geophysical siting procedures in 16 locations in Kamuli District, eastern Uganda. Boreholes that were sited after applying appropriate geophysical techniques yielded adequate quantities of water, whereas those sited where such procedures were not applied were out of service sooner than expected. Techniques to determine the precise location of resistivity anomaly and vertical electrical sounding (VES) models were used to locate water-bearing zones. VESs were undertaken to provide an overview of the geology. The apparent resistivities of the water-bearing zones both from VES and resistivity profiling data, had a relationship with the success rates of the boreholes. Electrical resistivities were correlated with hydrogeological parameters. The majority of successful boreholes had, within water-bearing zones, minimum apparent resistivity values less than 200 and 100 Ohmm, from the resistivity profiling anomalies and VES, respectively. The depth to bedrock was generally greater than 20m below ground level, which indicates potential for medium yielding boreholes.
Keywords: Vertical electrical sounding . Geophysical methods . Groundwater exploration . Hydraulic properties . Uganda